FIRST RECORDS OF TWO SPECIES OF GENUS MESSOR FOREL, 1890 (F ORMICIDAE: MYRMICINAE) ALONG WITH TROPHIC ASSOCIATIONS WITH APHIDS FROM POTHWAR REGION OF PAKISTAN - I. Bodlah; M. T. Rasheed; X. Huang; A. Gull-E-Fareen J. A. Siddiqui; M. A. Bodlah (Journal of Animal and Plant Sciences, 2019)
Two species of genus Messor Forel, 1890, namely Messor instabilis (Smith, 1858) and Messor himalayanus (Forel, 1902) have been recorded for the first time from Pothwar region of Pakistan.  Trophic associations of both species with aphid partners are reported for the first time from Pakistan. Main identification characters supported with micro-photographs, measurements and distribution are given. A key to both species based on worker caste has also been given.
Keywords: New records; Messor; Hymenoptera; Myrmicinae; Trophic associations; Pothwar; Pakistan